WAYS TO DEVELOP EXPRESSIVE READING SKILLS IN STUDENTS - Abdurakhmonova , Munira (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
Developing expressive reading skills in students is considered one of the important pedagogical tasks in the process of primary education. Expressive reading helps students deeply understand the meaning of a text, improve speech fluency, develop correct pronunciation, and form artistic taste. In particular, during primary school years, learning to use tone of voice, pauses, stress, and intonation correctly creates the foundation for successful reading competence in later stages of education. This article analyzes effective ways, innovative methods, and practical exercises for developing expressive reading skills in students. The research findings show that role-based reading, the use of audio texts, memorizing poems, dramatization, and individual exercises significantly improve students’ expressive reading abilities. In addition, regular practice and motivational approaches increase students’ interest in reading.